Preferensi Pangan Rumah Tangga Berdasarkan Sosial Ekonomi Wilayah di Kalimantan Barat - Imelda Wynalda; Rakhmad Hidayat (Master Program of Food Science and Technology, Faculty of Agricultural Technology, Udayana University, 2017)
This research aim to identify the society food preferences at the level of households based onper capita income of the region in the West Kalimantan province. The research method usedwas cross sectional study. The location of the research is grouped into three strata of theeconomy based on GDP, namely Pontianak city (high strata), Sekadau district (the lowerstrata) and Ketapang district (the intermediate strata). Then selected two subdistrict fromeach city/district. The sample of subjects is selected by purposive 25 householdsper subdistrict, and the total sample 150 households. The results showed that the foodpreferences of the subject significantly associated with per capita income of the area (p<0.05), namely corn, noodle, cassava, sweet potato, taro, sago, beef, chicken, duck egg, freshfish, shrimp, shellfish, anchovies, fish with soy, milk, milk powder, cooking oil, coconut,pecans, walnuts, chocolate, green beans, douchi fermented beans, granulated sugar, brownsugar, syrup, instant drinks, string beans, carrots, bananas, papaya, guava, mango, jackfruit,coffee and tea. Reasons for the selection of food preferences of the subject, because thehabits and the daily food.